2016
DOI: 10.1001/jamasurg.2016.1130
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery for Patients With Early-Onset vs Late-Onset Type 2 Diabetes

Abstract: This article describes the largest long-term study examining bariatric surgery for patients with early-onset T2DM. Bariatric surgery may achieve better and more long-lasting glycemic control in select patients with early-onset T2DM than in those with late-onset T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…As these patients tend to have severe disease and more complications, metabolic surgery is especially worth in this group of patients. A recent study showed that young onset (<40 years age) T2DM Asian had more severe disease than late onset T2DM patients but had a better response to metabolic surgery [58]. This study highlighted the importance of metabolic surgery to be considered as priority for those Asian with young onset and poorly controlled T2DM.…”
Section: Predictors Of Diabetes Remission and Patient Selectionmentioning
confidence: 90%
“…As these patients tend to have severe disease and more complications, metabolic surgery is especially worth in this group of patients. A recent study showed that young onset (<40 years age) T2DM Asian had more severe disease than late onset T2DM patients but had a better response to metabolic surgery [58]. This study highlighted the importance of metabolic surgery to be considered as priority for those Asian with young onset and poorly controlled T2DM.…”
Section: Predictors Of Diabetes Remission and Patient Selectionmentioning
confidence: 90%
“…With respect to diabetes resolution, several studies have similarly suggested that shorter duration of type 2 diabetes and higher preoperative C-peptide concentration are associated with greater diabetes resolution postoperatively 91 . Along with younger age, which has also been shown to be a positive predictor of better weight loss success 91 , 92 , this suggests that obese diabetic patients benefit from earlier intervention. These findings give credence to the argument that delaying bariatric surgery until individuals reach a BMI of more than 40 kg/m 2 may be counterproductive and actually be hurting more people in the end.…”
Section: Unanswered Questions and Future Investigationmentioning
confidence: 99%
“…This is concerning as young-onset type 2 diabetes (T2D) is an aggressive disease with increased risk of severe complications and high mortality [29]. Since bariatric surgery has proven effective for the remission and amelioration of young-onset T2D [30], this may indicate an underutilization of bariatric surgery in this particular sub-group, even within the wider context of a widespread underutilization of bariatric surgery, as highlighted among 14-25 year olds with obesity in the United States [31].…”
Section: Discussionmentioning
confidence: 99%